Compatibility of Pedagogical Technologies and Speech Culture: Innovative Approaches in English Language Teaching - Talipova Nilufar Abduvasikovna (Scientific Trends, 2025)
This article provides a comprehensive review of pedagogical technologies aimed at developing the professional speech culture of future English language teachers. First of all, the concept of speech culture, which is one of the personal and professional characteristics of an English language teacher, is explained. Speech culture is the ability to present vocabulary, accuracy in pronunciation, indicators, arguments, English facts in a coherent and understandable form, as well as the ability to express a sincere attitude in pedagogical communication with students. In delivering English lessons to students, working with English language sources, expressing the characteristics of the era, and thoroughly revealing cause-and-effect relationships are of particular importance. The article emphasizes the importance of strengthening the fluency and expressiveness of speech, teaching students the skills of making meaningful, clear and attractive speeches.
Keywords: Teacher, pedagogical technology, professional speech culture, interactive method, speech competence, pedagogical ethics, game, innovative technology, technological tools, methods, techniques